Molecular analysis of idiopathic subglottic stenosis for Mycobacterium species. (14th June 2016) - Gelbard, Alexander; Katsantonis, Nicolas‐George; Mizuta, Masanobu; Newcomb, Dawn; Rotsinger, Joseph; Rousseau, Bernard; Daniero, James J.; Edell, Eric S.; Ekbom, Dale C.; Kasperbauer, Jan L.; Hillel, Alexander T.; Yang, Liying; et al.
Abstract : Objectives/Hypothesis: Idiopathic subglottic stenosis (iSGS) is an unexplained obstruction involving the lower laryngeal and upper tracheal airway. Persistent mucosal inflammation is a hallmark of the disease. Epithelial microbiota dysbiosis is found in other chronic inflammatory mucosal diseases; however, the relationship between tracheal microbiota composition and iSGS is unknown. Given the critical role for host defense at mucosal barriers, we analyzed tissue specimens from iSGS patients for the presence of microbial pathogens. Methods: Utilizing 30 human iSGS, 20 intubation‐related tracheal stenosis (iLTS), and 20 healthy control specimens, we applied molecular, immunohistochemical, electron microscopic, immunologic, and Sanger‐sequencing techniques. Results: With unbiased culture‐independent nucleic acid, protein, and immunologic approaches, we demonstrate that Mycobacterium species are uniquely associated with iSGS. Phylogenetic analysis of the mycobacterial virulence factor rpoB suggests that, rather than Mycobacterium tuberculosis, a variant member of the Mycobacterium tuberculosis complex or a closely related novel mycobacterium is present in iSGS specimens. Conclusion: These studies identify a novel pathogenic role for established large airway bacteria and provide new targets for future therapeutic intervention. Level of Evidence: NA Laryngoscope, 127:179–185, 2017